2014
DOI: 10.4317/medoral.19595
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of squamous cell carcinoma of the lower lip: An experience of 109 cases

Abstract: Objectives: We are presenting our experience collected from a series of 109 cases with SCC of the lower lip focusing on clinical features of patients and surgical approach. Study Design: We retrospectively analyzed medical records of patients diagnosed with Squamous Cell Carcinoma (SCC) of the lower lip at the Oral and Maxillofacial surgery at Xi’an Jiaotong University during a period between 1999 and 2008. Results: A total of 109 patients with lip cancer were included in the study. When no frozen-section test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…The main indication for the elective neck dissection in head and neck cancer is the presence of the risk of lymph node metastases more than 20% (Shah & Gil, ). Thus, in many clinics, surgery of the primary tumor with “wait and see” policy in terms of neck treatment is the most common treatment in the early‐stage lip cancer (Eskiizmir et al, ; Rena et al, ). In a recent meta‐analysis of the literature about the early‐stage lip cancer with N 0 neck, the rate of occult lymph node metastases was reported as 17% of the patients who underwent elective neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The main indication for the elective neck dissection in head and neck cancer is the presence of the risk of lymph node metastases more than 20% (Shah & Gil, ). Thus, in many clinics, surgery of the primary tumor with “wait and see” policy in terms of neck treatment is the most common treatment in the early‐stage lip cancer (Eskiizmir et al, ; Rena et al, ). In a recent meta‐analysis of the literature about the early‐stage lip cancer with N 0 neck, the rate of occult lymph node metastases was reported as 17% of the patients who underwent elective neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated 57 patients with lip cancer and reported that radical tumour resection was viable for those with T 1 stage disease; neck dissection was not necessary in terms of satisfactory oncological outcomes 19 . Another study detected regional recurrence in only 2 cases (out of 91, 2.1 per cent); the authors suggested that the implementation of an ‘ultrasound-assisted wait and see’ policy was appropriate for clinical stage T 1‒2 N 0 patients 20 . In the present study, all patients with early-stage lip cancer underwent ‘ultrasound-assisted wait and see’ evaluation in terms of neck status; 1 pathological stage T 1 patient (out of 33, 3.0 per cent) and 1 pathological stage T 2 patient (out of 8, 12.5 per cent) experienced locoregional recurrence during follow up.…”
Section: Discussionmentioning
confidence: 99%
“…110,109 Treatment includes surgical excision with neck dissection for high grade tumors or those with palpable lymph nodes. 111,112 Radiation therapy has outcomes similar to surgery for lip tumors and is a good option for non-surgical candidates. Radiation therapy, however, does not allow for histologic confirmation.…”
Section: Squamous Cell Carcinoma Of the Lipmentioning
confidence: 99%